2009
DOI: 10.1007/s12525-009-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Information search and paid results — proposition and test of a hierarchy-of-effect model

Abstract: Search engines stand as the first entry point to internet resources for 70% of users. The results page is therefore an appealing place for advertising in the form of sponsored links also called paid results. Yet little academic knowledge has been developed to understand users' perceptions and behaviors toward sponsored links. In particular it is of foremost importance to delineate factors that influence click intention and behavior. This paper proposes a hierarchy-of-effects model in order to understand surfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
3
0
2
Order By: Relevance
“…Several models based on historical click data are limited in that they lack consideration of a possible user learning effect. Taking Gauzente's results as an example, it has been shown that past user satisfaction with Paid Search results influences current click behavior (Gauzente, 2009). In addition to the incorporation of position data and the perceived relevance of presented ads, the CT R of an advertisement is also affected by the relationship between organic and Paid Search results.…”
Section: Paid Search Advertisingmentioning
confidence: 99%
“…Several models based on historical click data are limited in that they lack consideration of a possible user learning effect. Taking Gauzente's results as an example, it has been shown that past user satisfaction with Paid Search results influences current click behavior (Gauzente, 2009). In addition to the incorporation of position data and the perceived relevance of presented ads, the CT R of an advertisement is also affected by the relationship between organic and Paid Search results.…”
Section: Paid Search Advertisingmentioning
confidence: 99%
“…La publicidad en los medios en internet presenta algunas peculiaridades. En los buscadores la experiencia, ratificada por los pocos estudios disponibles (Gauzente, 2009), parece indicar que los internautas no la sienten como un problema. Sin evidencia científica podría aventurarse que la causa más probable de esta actitud es que su presencia no dificulta el llegar a los resultados puros 7 (aunque esto podría ser debatible en el caso de búsqueda en dispositivos de pantalla reducida).…”
Section: La Publicidad Personalizada Como Modelo De Negocio En La éPounclassified
“…Several models based on historical click data suffer from limitations in terms of lacking consideration of a possible user learning effect. Taking Gauzente's results as an example, it has been shown that past user satisfaction with Sponsored Search results influences the current click behaviour (Gauzente, 2009). Besides the incorporation of position data and the perceived relevance of presented ads, the CT R of an advertiser is also affected by the relationship between organic and Sponsored Search results.…”
Section: Click Probabilitymentioning
confidence: 99%